Relationships between botanical composition, yield and forage quality of permanent grasslands over the first growth cycle. (6th August 2015) - Andueza, D.; Rodrigues, A. M.; Picard, F.; Rossignol, N.; Baumont, R.; Cecato, U.; Farruggia, A.
Abstract: This study examined the relationships between botanical composition and forage parameters (yield and forage quality variables) in 153 permanent grasslands located in the Massif Central of France. Grasslands were sampled at two vegetation stages in the first growth cycle. Botanical composition, yield, ash, crude protein, neutral detergent fibre, acid detergent fibre, acid detergent lignin, organic matter digestibility (OMD) and voluntary intake (VI) were estimated for each sample. Temporal variability in species–forage parameter relationships were accounted for using innovative multivariate analyses applied mainly in ecological science. Crude protein and OMD were weakly correlated when each harvest time was analysed separately. Species–forage parameter relationships remained stable during the first growth cycle. The stability of these relationships indicates that permanent grasslands dominated by competitive species were associated with high yield and forage quality values whereas permanent grasslands composed of conservative species and/or high proportions of senescent material were associated with high structural carbohydrate values and low yield, OMD and VI values. Based on these relationships, we propose a typology of permanent grasslands along with a set of indicator species enabling non‐specialist botanists to easily classify grasslands for grassland management purposes.